Los ingresos municipales y su relación con el gasto público de la Municipalidad Distrital de Punchana durante el periodo 2016 – 2023 - Cauper Pereyra, Jerry Lois (2025)
During the 2016–2023 period, the Punchana District Municipality recorded total revenues of S/ 193,099,838.00 and expenditures of S/ 216,005,457.00, showing fluctuating budget execution. In annual terms, revenues had an average variation of 8.80%, while expenditures grew by an average of 3.12%. Despite some years with significant increases, such as in 2022, notable declines were also observed, especially in 2019 and 2020. This lack of consistency suggests a weak structural relationship between tax collection capacity and expenditure execution. According to the results of the Shapiro-Wilk normality test, both revenues and expenditures exhibit a normal distribution (p > 0.05), allowing for the use of parametric methods. Pearson's correlation analysis yielded a coefficient of r = 0.6390 between revenue and expenditure, representing a moderately positive relationship.